2004
DOI: 10.1037/0022-006x.72.4.698
|View full text |Cite
|
Sign up to set email alerts
|

Millon Clinical Multiaxial Inventory-III Subtypes of Opioid Dependence: Validity and Matching to Behavioral Therapies.

Abstract: The concurrent and predictive validity of 2 different methods of Millon Clinical Multiaxial Inventory-III subtyping (protocol sorting, cluster analysis) was evaluated in 125 recently detoxified opioid-dependent outpatients in a 12-week randomized clinical trial. Participants received naltrexone and relapse prevention group counseling and were assigned to 1 of 3 intervention conditions: (a) no-incentive vouchers, (b) incentive vouchers alone, or (c) incentive vouchers plus relationship counseling. Affective dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 75 publications
(145 reference statements)
3
19
1
Order By: Relevance
“…Such efforts have often identified four clinically coherent subgroups: high psychopathology, antisocial, neurotic, and subclinical (9)(10)(11)(12)(13)(14)(15)(16)(17). A high psychopathology subgroup has been found to be associated with comorbid psychiatric diagnoses including Post Traumatic Stress Disorder, greater depression, more suicide attempts, more previous psychiatric and drug treatments, and drug treatment nonresponse (8). An antisocial cluster subgroup has been linked with high alcohol consumption rates (13,16), serious alcohol problems (13), and drug treatment nonresponse in one study involving predominantly male Caucasian opiate abusers (8) but not in another in which African-American male participants were in the majority (18).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Such efforts have often identified four clinically coherent subgroups: high psychopathology, antisocial, neurotic, and subclinical (9)(10)(11)(12)(13)(14)(15)(16)(17). A high psychopathology subgroup has been found to be associated with comorbid psychiatric diagnoses including Post Traumatic Stress Disorder, greater depression, more suicide attempts, more previous psychiatric and drug treatments, and drug treatment nonresponse (8). An antisocial cluster subgroup has been linked with high alcohol consumption rates (13,16), serious alcohol problems (13), and drug treatment nonresponse in one study involving predominantly male Caucasian opiate abusers (8) but not in another in which African-American male participants were in the majority (18).…”
Section: Introductionmentioning
confidence: 98%
“…A high psychopathology subgroup has been found to be associated with comorbid psychiatric diagnoses including Post Traumatic Stress Disorder, greater depression, more suicide attempts, more previous psychiatric and drug treatments, and drug treatment nonresponse (8). An antisocial cluster subgroup has been linked with high alcohol consumption rates (13,16), serious alcohol problems (13), and drug treatment nonresponse in one study involving predominantly male Caucasian opiate abusers (8) but not in another in which African-American male participants were in the majority (18). Neurotic cluster subgroup membership has been linked to solitary drinking among alcohol abusers (12), and longer opiate use histories, more medical and psychological problems, and less favorable treatment response among opiate addicts (8).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the reviewers believe that the results of the Ball trial, 58 which reported only data-driven analyses rather than randomised comparisons, are uninterpretable for the purposes of informing the question about whether incentive vouchers enhance retention on naltrexone.…”
Section: Was Allocation Of Treatment Concealed?mentioning
confidence: 99%
“…Full details are not given of the programme in the Ball study, 58 but participants could earn up to $561 worth of goods if they completed the full CT, can't tell; N, no; NA, not applicable; Y, yes.…”
Section: Contingency Management Interventionsmentioning
confidence: 99%